Observation-based assessment of secondary water effects on seasonal vegetation decay across Africa - Küçük, Çağlar (2022)
Funding Information: ÇK acknowledges funding from the International Max Planck Research School for Global Biogeochemical Cycles. SK acknowledges the support of the Erdsystemforschung: Afrikanische Grundwasserressourcen im Zuge des globalen Wandels (Earth System Research: Groundwater Resources in Africa under Global Change) project of the Max Planck Society. Publisher Copyright: Copyright © 2022 Küçük, Koirala, Carvalhais, Miralles, Reichstein and Jung.